PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO MUNCUL KOMPUTER : PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO MUNCUL KOMPUTER - alpin yansah; Heri Haerudin (CV. Multi Kreasi Media, 2022)
Kata Kunci: Penjualan, Waterfall, PHP, MySQL Abstract− DESIGN OF WEB-BASED SALES INFORMATION SYSTEM AT COMPUTER POPULAR STORE). Selling is a process in which the seller fulfills all the needs and desires of the buyer to achieve the sustainable benefits of the seller and the buyer that benefits both parties. In the increasingly rapid development of technology, the role of technology is expected to be able to assist companies in managing sales report data, making customer purchase notes, especially in computerized stores. However, at this time the shop appeared. Computers still use book media as a media for storing sales report data, in making customer purchase notes, it is still manually recorded. These obstacles can be overcome by using current technology. One of them is by utilizing web-based technology. Therefore, the author wants to design a website-based sales information system that is expected to be used at the Muncul Computer Store. The development of this application uses the waterfall method and for programming it uses the PHP programming language and MySQL database. The results of this study are in the form of a web-based sales information system that can be useful for making it easier to make sales reports and notes on computerized stores. Keywords: Sale, Waterfall, PHP, MySQL